MUJERES EN EMBARAZO, PARTO, Y POSPARTO: UNA MIRADA DESDE EL PENSAMIENTO FEMINISTA. - Bedoya-Ruiz, Libia A.; Agudelo-Suárez, Andrés A.; Restrepo-Ochoa, Diego A. (Revista Peruana de Medicina Experimental y Salud Pública, 2020)
This essay analyzes the contributions of the gender approach of feminist thinking to understand the relationship of women in pregnancy, childbirth, and postpartum with health service personnel. Original qualitative design research was analyzed, were the relationship of women with health personnel is visualized. It is concluded that the gender approach of feminist thinking is a useful approximation to understand the problem of women's relations with health service personnel in aspects such as obstetric violence, care and the intersection of gender with other categories, in the framework of the health system.